Geographic Variation of Chronic Kidney Disease Prevalence: Correlation with the Incidence of Renal Cell Carcinoma or Urothelial Carcinoma?. (28th October 2015) - Yap, Yit-Sheung; Chuang, Kai-Wen; Chiang, Chun-Ju; Chuang, Hung-Yi; Lu, Sheng-Nan
Abstract : Background . The aim of this study is to evaluate whether geographic variations in the prevalence of late-stage chronic kidney disease (CKD) exist and are associated with incidence rates of renal cell carcinoma (RCC), upper tract urothelial carcinoma (UTUC), or lower tract urothelial carcinoma (LTUC). Methods . Prevalence rates of late-stage CKD for 366 townships (n > 30 ) in Taiwan were calculated for 1, 518, 241 and 1, 645, 151 subjects aged 40 years or older in years 2010 and 2009, respectively. Late-stage CKD prevalence in year 2010 was used as a training set and its age-adjusted standardized morbidity rates (ASMR) were divided into three groups as defined <1.76%, 1.76% ≤ ASMR < 2.64%, and ≥2.64%, respectively. Year 2009, defined as the validation set, was used to validate the results. Results . The ASMR of late-stage CKD in years 2010 and 2009 were 1.76%, and 2.09%, respectively. Geographic variations were observed, with notably higher rates of disease in areas of the central, southwestern mountainside, and southeastern seaboard. There were no significant differences among different combined risk groups of RCC, UTUC, and LTUC incidence. Conclusion . The substantial geographic variations in the prevalence of late-stage CKD exist, but are not correlated with RCC, UTUC, or LTUC incidence.